Comparative Efficacy of Saga Seed-Derived Media in Supporting Staphylococcus aureus and Escherichia coli Growth - Rahmah, Lestari; Noor, Vuan Sindra; Sari, Tania Regita; Putra, Geminsah; Sembiring, Febri (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
Saga seeds possess a high protein content, presenting a potentially economical substrate for microbiological medium development. This study evaluated the suitability of saga seeds (Adenanthera pavonina) as an alternative culture medium for propagating Escherichia coli and Staphylococcus aureus. The objective was to determine whether medium derived from saga seeds could sustain bacterial proliferation at levels comparable to conventional medium. It was postulated that both flour-based and infusion-based saga seed medium would yield bacterial growth statistically indistinguishable from that on Tryptic Soy Agar (TSA). Two formulation methods were examined: a flour-based medium and an infusion-based medium. E. coli and S. aureus were cultured on these alternative media and benchmarked against TSA. Colony-forming units (CFUs) were quantified and statistically analyzed using an independent samples t-test. The infusion-based medium displayed complete solubility with no residue, whereas the flour-based variant showed sedimentation. Colonies on both saga-based media appeared white, circular, and approximately 3 mm in diameter, consistent with those on the control medium. Based on productivity rate standards, both the saga seed medium fulfilled the minimum criteria for a non-selective medium. After adjusting for dilution, E. coli reached 1.06 × 10⁵ CFU/ml on the flour-based medium, exhibiting no statistically significant deviation from TSA. In contrast, the infusion-based medium supported lower E. coli growth at 0.94 × 10⁴ CFU/ml. S. aureus growth on the flour-based (1.08 × 10⁵ CFU/ml) and infusion-based medium (1.04 × 10⁵ CFU/ml) did not significantly differ from the control. The flour-based saga medium offers a promising and effective alternative for cultivating E. coli and S. aureus. Nonetheless, further optimization is advised to improve the flour-based formulation's solubility and visual clarity.